La imprescriptibilidad de la infracción de privación ilegal de libertad y el principio de favorabilidad - Pereira Molina, Maybe Nazhaly (2018)
The present case analysis on the non-applicability of the statute of limitations for the infringement of illegal deprivation of liberty committed in the year 1985, has an investigation and analysis of the conviction of the judge of the Judicial Unit of Criminal Guarantees of El Oro in 2017, with headquarters in the Machala canton, in which the principle of favorability for the accused is violated, because in 2009 the statute of limitations for the crime committed in 1985 was requested, a prescription that was accepted by both the Third Criminal Judge of El Oro and ratified by the Third Chamber of Criminal Matters of El Oro, therefore the defendant's desire is that the statute of limitations granted in 2009 be carried out as valid proof, but when sentencing the defendant is sentenced to two months of prison, violating this constitutional principle, adducing the Judge of the Judicial Unit of Criminal Guarantees of El Oro that the crime is imprescriptible for being a serious violation to the Rights Humans, without citing the express norm that typifies the imprescriptibility of the illegal deprivation of liberty, leaving a legal vacuum at the moment of sentencing. Our research will be developed according to international treaties ratified by the Ecuadorian State, laws, doctrine, judgments, scientific journals and comparative law to clarify whether the conviction is based on law or if there are errors in the criminal process. The principle of favorability is of direct application, is protected by our Constitution and International Treaties, being implausible that its application has been denied at the time of issuing sentence. In addition, the Rome Statute of the International Criminal Court, which describes which crimes are imprescriptible and, in turn, the non-retroactivity ratione personae, where no one will be criminally liable for conduct prior to the entry into force of the Statute, is incorporated into the investigation. This international standard is the key piece to solve one of the hypotheses raised in the investigation. There will also be an internal legislative evolution on the imprescriptible crimes typified in the Constitutions of 1979, 1998 and 2008, where the Constitution of 1979 did not cover the statute of limitations, it is in the year of 1998 that it is established that crimes are not subject to statute of limitations, but the present is not typified to the illegal deprivation of freedom as an imprescriptible crime. Similarly, the Criminal Code, Code of Criminal Procedure and Comprehensive Criminal Code evidences the ways to extinguish the criminal action, taking as a central point the prescription, being applicable in the year 1985 for the infraction described in previous lines, without impediment by international or national laws on that date. Finally, our investigation has developed an extensive content to verify whether the resolutions and judgments have been duly substantiated and has not violated rights, guarantees or principles of the procedural subjects or the process, presenting conclusions and possible solutions to the problems raised so as not to such irregularities are committed again in a criminal proceeding.